The immortal conquistador eaudiobook - Vaughn, Carrie (Tantor Media, 2020)
From Carrie Vaughn, author of the beloved Kitty Norville werewolf talk-show host series, comes the vampire origin story of Kitty's famed ally, Rick—and his sudden turn to darkness in the seventeenth century. More than 500 years before his friendship with Kitty, noble Ricardo de Avila's life met a fate-changing twist, and his morally-complex, blood-soaked existence as an immortal began. Before being turned, Ricardo de Avila would have followed Coronado to the ends of the earth. Instead he found the end of his mortal life—and a new one, as a renegade vampire. For over five hundred years as an immortal, Ricardo has followed his own moral code, upsetting the established order in the demon world. He has protected his found family from marauding evil, joined up with a legendary gunslinger, tended bar, appointed himself the Master of Denver, and discovered a church buried under the Vatican. The life of a vampire is frequently long, but for Rick, it is never easy.